The Effect of Slow-Release Fertilizer on the Growth of Garlic Sprouts and the Soil Environment - Chunxiao Han; Zhizhi Zhang; Renlong Liu; Changyuan Tao; Xing Fan (Applied Sciences)
To address the issue of excessive chemical fertilizer use in agricultural production, this study conducted a pot experiment with four treatments: CK (no fertilization), T1 (the application of potassium magnesium sulfate fertilizer), T2 (the application of slow-release fertilizer equal to T1), and T3 (the application of slow-release fertilizer with the same fertility as T1). The effects of these treatments on garlic seedling yield, growth quality, chlorophyll content, photosynthetic characteristics, and the soil environment were investigated to evaluate the feasibility of replacing conventional fertilizers with slow-release formulations. The results showed that compared with CK, all three fertilized treatments (T1, T2, and T3) significantly increased the plant heights and stem diameters of the garlic sprouts (p < 0.05). Plant height increased by 14.85%, 17.81%, and 27.75%, while stem diameter increased by 9.36%, 8.83%, and 13.96%, respectively. Additionally, the chlorophyll content increased by 4.34%, 7.22%, and 8.05% across T1, T2, and T3, respectively. Among the treatments, T3 exhibited the best overall growth performance. Compared with those in the CK group, the contents of soluble sugars, soluble proteins, free amino acids, vitamin C, and allicin increased by 64.74%, 112.17%, 126.82%, 36.15%, and 45.43%, respectively. Furthermore, soil organic matter, available potassium, magnesium, and phosphorus increased by 109.02%, 886.25%, 91.65%, and 103.14%, respectively. The principal component analysis indicated that soil pH and exchangeable magnesium were representative indicators reflecting the differences in the soil’s chemical properties under different fertilization treatments. Compared with the CK group, the metal contents in the T1 group slightly increased, while those in T2 and T3 generally decreased, suggesting that the application of slow-release fertilizer exerts a certain remediation effect on soils contaminated with heavy metals. This may be attributed to the chemical precipitation and ion exchange capacities of phosphogypsum, as well as the high adsorption and cation exchange capacity of bentonite, which help reduce the leaching of soil metal ions. In summary, slow-release fertilizers not only promote garlic sprout growth but also enhance soil quality by regulating its chemical properties.